Answer:
B.
Step-by-step explanation:
When reflecting over the x-axis:
(x, y) (x, -y)
The y changes signs (+, -)
Do you mean add are subtract
i will glad to help in comments
if you awnser
Answer:
x= -5, -12
Step-by-step explanation:
Answer:
x intercept is x=3
y intercept is y=-3
Step-by-step explanation:
We can write this equation in a simpler way to find the values needed. Lets do it. Take:
x-y=3
And sum y in both sides, as we know the equality will maintain:
x-y+y=3+y
x = 3+ y
Now subtract 3 in both sides:
x-3 = y+3-3
x-3=y
So, we can rewrite our equation as y=x-3
The x intercept is a value of x such that the equation in equal to zero; in other words, is the value of x when y is zero. It is also called a zero root. Graphically, its the x value when the function passes trough the x-axis. Lets find if, we nned that:
x-3 = 0
If we sum 3 in both sides:
x-3+3=3
x=3
So, x=3 is x intercept
For finding the y intercept we need the value of y when x is zero. Graphically, is the value of y obtained when the function passes trough the y-axis. So, replace x with 0:
0-3=y
y=-3
Another way to get it is knowing that the y intercept in a polynomial is always the independent term, the one that has no x or y, which in this case is -3.
Answer:
13
Step-by-step explanation:
Just In case you want explanation-
1. 4 squared Meaning 4 x 4 = 16
2. 16 x 6 = 96
3x 6 = 18
96- 18 = 78
in the denominator, 25/ 5 = 5
11 minus 5 = 6
78 divided by 6
it gives you 13